Investigating The Acceptance and Use of Performance Information System (SIP Bdg Juara) on Bandung City - Zati Woro Shabrina; Dini Turipanam Alamanda; Fajar Sidiq Adi Prabowo (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
Improving the utilization of ICT is one of many solutions proposed by The Municipal Government of Bandung to overcome urban problems. In its entirity, the concept is well-known as Bandung Smart City. There are many Smart Government programs that have been implemented in Bandung. One of them is Performance Information System of Bandung Juara or known as SIP Bdg Juara. But the acceptance of SIP Bdg Juara are relatively low. Furthermore, not all of the citizens have thoroughly understood the system. Hence, it is important to find out the acceptance of this website.This research uses modified UTAUT 2 model which was taken from the UTAUT 2 Theory by Venkatesh et al. (2012) that consist of seven main variables; Performance Expectancy, Effort Expectancy, Social Influence, Facillitating Conditions, Hedonic Motivation, Price value, and Habit. Moreover, two moderating variables of Age and Gender were also involved. This research used SEM-PLS method to analyze the data. For the data collection, questionnaires were distributed to 400 residents living in the city of Bandung as the respondents whether they have or have not participated yet in SIP Bdg Juara website. Finally, this study found that the most influential factor of interest in using SIP Bdg Juara website is Price Value, followed by Hedonic Motivation and then Habit in which all of those three factors have positive influence in both types of latent variables. While the variables affecting Use Behavior related to the use of SIP Bdg Juara wesite are Habit and Behavioral Intention. These findings are expected to provide valuable insights for The Government in improving the success rate of ICT-based governance programs. Keywords: Bandung Smart City, Modified UTAUT 2, SIP Bdg Juara, Techonology Acceptance